2012
DOI: 10.1117/12.911895
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric consideration for patients with dental filling materials undergoing irradiation of oral cavity using RapidArc: challenges and solution

Abstract: In this study, we investigate the effect of dental filling materials (DFM) on RapidArc TM treatment plans and delivery in a patient undergoing radiotherapy treatment. The presence of DFM creates uncertainties in CT number and causes long streaking artifacts in the reconstructed images which greatly affect the dose distribution inside the oral cavity. The influence of extensive dental filling artifacts on dose distribution was performed using a geometrically well defined head and neck IMRT verification phantom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The presence of the DFM and its effect on dose calculation in RapidArc treatment planning was assessed in a phantom-based study by Mail et al (2012). They reported percent depth dose (PDD) data in the site of DFM measured with Gafchromic EBT2 film and a parallel-plate (PP) ion chamber.…”
Section: Ct Artifacts From Dental Implantsmentioning
confidence: 99%
“…The presence of the DFM and its effect on dose calculation in RapidArc treatment planning was assessed in a phantom-based study by Mail et al (2012). They reported percent depth dose (PDD) data in the site of DFM measured with Gafchromic EBT2 film and a parallel-plate (PP) ion chamber.…”
Section: Ct Artifacts From Dental Implantsmentioning
confidence: 99%
“…Specifically, the mask improved the dose homogeneity while the virtual filter enhanced the delivered dose to the target tumor. These findings were obtained from the phantom and patient studies using RapidArc RT plans in the successive studies by Mail et al 9,10 In another dental phantom study by Maerz et al, dose distribution deviations were calculated in both IMRT and volumetric modulated arc therapy (VMAT) plans generated from metal artifact-contaminated CT images. 11 Their study also concluded that RT plans created from metal artifact-corrected CT images resulted in a significant decrease in dose perturbations for the H&N cases.…”
mentioning
confidence: 99%